2012
DOI: 10.1371/journal.pone.0040168
|View full text |Cite
|
Sign up to set email alerts
|

Sensing of Fatty Acids for Octanoylation of Ghrelin Involves a Gustatory G-Protein

Abstract: BackgroundGhrelin is an important regulator of energy – and glucose homeostasis. The octanoylation at Ser3 is essential for ghrelin’s biological effects but the mechanisms involved in the octanoylation are unknown. We investigated whether the gustatory G-protein, α-gustducin, and the free fatty acid receptors GPR40 and GPR120 are involved in the fatty acid sensing mechanisms of the ghrelin cell.MethodsWild-type (WT) and α-gustducin knockout (gust−/−) mice were fed a glyceryl trioctanoate-enriched diet (OD) dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
74
0
10

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 69 publications
(84 citation statements)
references
References 46 publications
0
74
0
10
Order By: Relevance
“…The second is the suppression of octanoylated ghrelin secretion regulated by signaling via G protein-coupled receptor 120 GPR120 and α-gustducin. GPR120, which functions mainly as a receptor for unsaturated longchain fatty acids 30 , could play a role in the lipid sensing cascade in ghrelin-producing cells 31 . The decrease in octanoylated ghrelin secretion after feeding is partially induced by long-chain fatty acids that act directly on gastric GPR120-expressing ghrelin cells 32 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The second is the suppression of octanoylated ghrelin secretion regulated by signaling via G protein-coupled receptor 120 GPR120 and α-gustducin. GPR120, which functions mainly as a receptor for unsaturated longchain fatty acids 30 , could play a role in the lipid sensing cascade in ghrelin-producing cells 31 . The decrease in octanoylated ghrelin secretion after feeding is partially induced by long-chain fatty acids that act directly on gastric GPR120-expressing ghrelin cells 32 .…”
Section: Discussionmentioning
confidence: 99%
“…The decrease in octanoylated ghrelin secretion after feeding is partially induced by long-chain fatty acids that act directly on gastric GPR120-expressing ghrelin cells 32 . In addition, it was reported that the G protein α-gustducin is also involved in ghrelin octanoylation 31 and that α-gustducin could couple GPR120 33 . In our study, stearic acid, oleic acid, linoleic acid, and α-linolenic acid could have suppressed the release of octanoylated ghrelin via GPR120 and/or α-gustducin-mediated mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, ghrelin secretion might be regulated by hormonal, neuronal, and metabolite signals that arise from nutrient sensing and absorption in the intestine. In fact, in support of this view, recent studies have shown that nutrients (i.e., fatty acids and glucose) and hormones (i.e., insulin and oxytocin) regulate ghrelin secretion in fluorescence-activated cell sorting-separated primary mouse ghrelin cells and ghrelinoma cell lines (i.e., SG-1, PG-1, and mouse ghrelinoma 3-1 (MGN3-1)) (Janssen et al 2012, Sakata et al 2012.…”
mentioning
confidence: 88%
“…Free fatty-acid receptors are involved in control of various gastrointestinal hormones by fatty acids [80], and that also seems to be the case with ghrelin. The long-chain fatty-acid receptor FFAR4 (GPR120), but not FFAR1 (GPR40), is expressed in ghrelin-producing cells [32, [127][128][129]. Knockdown of FFAR4 attenuates α-linolenic acid-induced suppression of ghrelin secretion from MGN3-1 or SG-1 cells [128,129].…”
Section: Fatty Acidsmentioning
confidence: 99%
“…The long-chain fatty-acid receptor FFAR4 (GPR120), but not FFAR1 (GPR40), is expressed in ghrelin-producing cells [32, [127][128][129]. Knockdown of FFAR4 attenuates α-linolenic acid-induced suppression of ghrelin secretion from MGN3-1 or SG-1 cells [128,129]. The FFAR4 agonists GW-9508 and compound B suppress ghrelin secretion in vitro [32,129], but not in gastric mucosal cells of FFAR4-knockout mice [32].…”
Section: Fatty Acidsmentioning
confidence: 99%